Analisis Interaksi Sosial Mahasiswa Pelanggan Aplikasi Tiktok - Eka Susanti; Sarah Lailatil Fadla; Leni Hermita Hasibuan; Nadhilah Ajrina; Elvi Azizah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
TikTok is the newest social media application that allows users to create interesting videos, interact in comments and private chat. The purpose of writing this article is to analyze the role of the TikTok application as a medium for interaction, the impact of the TikTok application on students social interaction, and wise strategies for becoming a TikTok applicatin customer. The research methode used is a qualitative method, namely research carried out through observation and searchng for data directly. The result of this research show that, 1) the TikTok application has a role as a medium for carrying out interaction processes, for example increasing friendships, getting motivation from shared content, finding people with the same vision; 2) one of the negative impacts of TikTok is the lack of direct social interaction because users are engrossed in the application. Meanwhile, the positive impact is the establishment of a friendship which then gives each other a good influence; 3) strategy to become a good TikTok costumer, namely by creating content that can attract the attention of other TikTok cutomers, for example creating content selling food, clothing and others, following positive accounts and using the TikTok application for creativity and innovation.